Bioequivalence Study of a Generic Quetiapine (Ketipinor®) and the Innovator Preparation (Seroquel®) 200 mg Given Orally in Healthy Thai Male Volunteers - Charuwan Pradabsang (Prince of Songkla University, 2016)
Thesis (M.Sc., Pharmacology)--Prince of Songkla University, 2010